Mapping fertiliser consumption dynamics in India: A spatial and temporal assessment - B, HARISH; K V, PRAVEEN; SINGH, ALKA; JHA, GIRISH KUMAR; SAHU, SUBHASHREE; ANBUKKANI, P; MATTOO, GAURAV (The Indian Journal of Agricultural Sciences, 2026)
Fertiliser use is central to India’s agricultural productivity, yet it’s spatial distribution remains highly uneven. Understanding these disparities is crucial for promoting balanced nutrient management. While earlier researches have focused mainly on national or state aggregates, district-level spatial patterns have received limited attention. This study fills that gap by examining long-term trends and spatial clustering in nitrogen, phosphorus, and potassium consumption across India. National and state-level trajectories are analysed through compound annual growth rates. District-level spatial analysis was conducted using Global Moran’s I and Getis-Ord Gi* hotspot analysis for the benchmark years 2013 and 2023. Results showed that although national growth rates have slowed, absolute fertiliser use continues to rise. State-level patterns reveal widening divergence with rapid expansion in central and eastern states and slower or negative growth in parts of the south and north-east states. Moran’s I values indicates significant and strengthening spatial autocorrelation for all nutrients. Hotspot maps highlight distinct nutrient geographies with nitrogen intensifying across the Indo-gangetic plain and southern high-input belts; phosphorus consolidating across central and southern states and potassium remaining concentrated in the southern peninsula. These spatially differentiated patterns call for fertiliser policy frameworks that move beyond uniform directives toward region and nutrient-specific strategies. Such policies should align soil health goals with crop nutrient requirements, while improving input efficiency, reducing imbalances, and sustaining farm productivity across India’s diverse agro-ecologies.